TAKING ADVANTAGE OF STUDENTS’ NATIVE LANGUAGES, ACTIONS, PICTURES, AND QUESTIONS TO HELP STUDENTS MASTER PRESENT PROGRESSIVE - Suswati Hendriani (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Teaching English Tenses to Indonesian students is not easy. It is even  a quite more challenging task for a teacher who teaches grammar when the teaching of grammar is aimed at making the students able to use the Tenses to communicate in the foreign language. The different grammar systems that Bahasa Indonesia and English have, have caused difficulties for the English teacher to teach English Tenses to Indonesian students. What should the teacher do to overcome  the difficulties? There are many possibilities that he or she can do. Yet, as a good teacher, he or she should try to find effective approaches to help his or her students master English Tenses. One of the Tenses that  EFL students should master is Present Progressive? How to teach the Tense to make the EFL students master the Tense (can use the tense in communication)? Based on the writer’s experience in teaching the Tense, students’ native language, actions, pictures, and questions help very much. This paper, therefore, is written to show the readers the way to teach Present Progressive by taking advantage of the students’ native language, actions, pictures, and questions.